Type of perception vs. lunge in fencing technique structure - Borysiuk, Z. (Revista de Artes Marciales Asiaticas, 2016)
The specific fencing duel is based on fencers' response on the three particular kinds of stimuli such as: visual, kinesthetic and acoustic. Functional efficiency of senses which are responsible for perception processes is the main condition of gaining achievement in sports. Moreover the above mentioned analyzers are the significant elements to excellence fencing techniques. Although, visual perception is not the only factor playing an important role when trying to anticipate the contestants' intentions. Many of actions undertaken during a fencing fight (e.g., cuts, binds and parries) require high level of kinesthetic feeling in other words appropriate responses on tactile stimulation. Significant part of actions' preparation depends on mastering sense of rhythm during the fight which should be followed by acoustic stimuli perception from foot work and technique actions performed by fencing weapon (Hassan & Klauck, 1998; Do & Yiou, 1999). Expression of different stimuli which is observed on the training and competitive surroundings demand particular cautions and the ability of attention divisibility from fencers. The results coming from various experiments prove that athletes respond on tactile stimuli in comparison with visual stimuli in the shortest time. The differentiation is estimated approximately from 100 to 120 ms. We observe slight variation in reference to information processes in response to acoustic and tactile stimuli to gain 10-15 ms (Borysiuk & Waskiewicz, 2008).